Binary alloy of virus capsids and gold nanoparticles as a Mie-resonance-based optical metamaterial. (February 2015) - Yannopapas, Vassilios
Abstract: We present a metamaterial design based on a binary alloy of gold nanoparticles and virus capsids (protein nanoparticles) which possesses metamaterial functionalities in the optical regime. Such binary alloys have already been realized in the laboratory by means of DNA-programmed crystallization of metallic nanoparticles and virus capsids with suitable DNA linkers. The resulting binary alloy has a NaTl-lattice symmetry and operates as Mie resonance-based metamaterial thanks to the extremely high values of the electric permittivity of the virus capsids. By employing an effective-medium theory and rigorous electrodynamic calculations we identify regions of photo-induced magnetic activity stemming from the Mie resonances of the virus capsids. The magnetic activity of the virus particles accompanied by the ordinary electric activity of the gold nanoparticles results in spectral regions of negative refractive index which can be tuned to a desired spectral window by varying the concentration of the RNA within the virus capsids.